Bridging STEM and Culture: The Role of Ethnoscience in Developing Critical Thinking and Cultural Literacy - Atmojo, Setyo Eko; Anggriani, Mitha Dwi; Rahmawati, Rina Dyah; Skotnicka, Michalina; Wardana, Ari Kusuma; Anindya, Agista Putri (Jurnal Pendidikan IPA Indonesia, 2025)
The lack of integration between science and local wisdom in science education remains a challenge in developing students' critical thinking skills and cultural literacy. This study aims to analyze the effect of STEM-based science learning integrated with ethnoscience on critical thinking skills and cultural literacy of elementary school students. This research is a quantitative study with a quasi-experimental method using a nonequivalent control group design. Samples were selected purposively and consisted of experimental and control groups. The instruments used include a critical thinking skills test and a cultural literacy questionnaire. Data analysis was performed using a paired sample t-test. The results showed a significant difference in posttest scores between the experimental and control groups, with a significance value of 0.000 <0.005. The average difference was 19.78 points for critical thinking skills (81.14 - 61.36) and 16.86 points for cultural literacy (82.50 - 65.64). This finding suggests that integrating STEM-based science learning with ethnoscience can significantly enhance students' critical thinking skills and cultural literacy. The novelty of this study lies in the learning approach that combines the STEM framework with local ethnoscience values, providing an innovative alternative for shaping students who think reflectively while developing cultural awareness from an early age.